Prevalence and Determinants of Dental Anxiety among Medical and Dental Students at Sirte University: A Cross-Sectional Study - Khyria Dhaw; Karima Alfitory; Nadia Rahouma (AlQalam Journal of Medical and Applied Sciences, 2026)
Dental anxiety is a common psychological condition that negatively affects dental attendance and oral health outcomes. It is particularly relevant among healthcare students, as their perceptions may influence future patient care. The Objective of this study is to assess the prevalence of dental anxiety and identify associated factors among medical and dental students at Sirte University. A cross-sectional study was conducted among 182 undergraduate students (88 medical and 94 dental students). Data were collected using a structured questionnaire incorporating the Modified Dental Anxiety Scale (MDAS). Anxiety levels were categorized as low (5–11), moderate (12–18), and high (≥19). Statistical analysis was performed using SPSS version 25, and associations between variables were assessed using the Chi-square test, with a significance level set at p < 0.05. Overall, 47.3% of students reported moderate anxiety, 39.0% low anxiety, and 13.7% high anxiety. Female students exhibited significantly higher levels of anxiety compared to males (p = 0.005). This trend was consistent among both medical (p = 0.041) and dental students (p = 0.024). No significant difference in anxiety levels was observed between medical and dental students overall (p = 0.700), nor across academic stages. Invasive procedures, particularly tooth drilling (42.3%) and local anesthetic injection (56.1%), were identified as the most anxiety-provoking, whereas scaling and polishing elicited the lowest anxiety levels. Dental anxiety is prevalent among students, with gender emerging as a significant associated factor. The type of dental procedure strongly influences anxiety levels, with invasive interventions generating the highest anxiety. These findings highlight the importance of targeted behavioral strategies and anxiety management approaches to improve dental care acceptance and outcomes.